TELAAH KURIKULUM BAHASA ARAB SLTP DAN SLTA DI ERA NEW NORMAL PROPINSI JAWA TENGAH - Darul Qutni; Muchlisin Nawawi (Lisanul Arab: Journal of Arabic Learning and Teaching, 2022)
The New Normal Era, or a new normal life, means that we can carry on with our normal activities as before being hit by Covid-19, but still have to apply health protocols. Policy makers also have to decide something that can save the lives of education actors, namely teachers and students, because it is related to the future of the nation's generation. Policies issued in the face of the New Normal Era, must be made carefully and carefully. Children's rights must be a priority, namely the right to a full, safe and healthy education. Children are the nation's assets, very valuable reformers, the hope and future of the nation are in their hands. Based on the above, the Middle School and Senior High School Arabic curriculum in this new normal era experienced several problems, including how to implement the Junior and Senior High School Arabic curriculum in the new normal era in Central Java province? What are the problems with implementing the Arabic language curriculum for junior and senior high schools in the new normal era in the province of Central Java? How to evaluate the implementation of the Arabic language curriculum for junior and senior high schools in the new normal era in the province of Central Java? The data collection methods in this study were observation, interviews and questionnaires. Middle and high school Arabic curriculum in the new normal era, namely mastery of technology. Arabic learning materials that are not suitable for learning media. Internet access Motivation In conducting curriculum evaluation it is necessary to adhere to the following principles: (1). Evaluation refers to the objective (2). Evaluation is comprehensive or thorough (3). Evaluation is carried out objectively.